National Association of Medical Examiners Position Paper: Recommendations for the Investigation, Diagnosis, and Certification of Deaths Related to Opioid Drugs. Issue 1 (March 2013) - Davis, Gregory G.; ,
The American College of Medical Toxicology and the National Association of Medical Examiners convened an expert panel to generate evidence-based recommendations for the practice of death investigation and autopsy, toxicological analysis, interpretation of toxicology findings, and death certification to improve the precision of death certificate data available for public health surveillance. The panel finds the following: 1. A complete autopsy is necessary for optimal interpretation of toxicology results, which must also be considered in the context of the circumstances surrounding death, medical history, and scene findings. 2. A complete scene investigation extends to reconciliation of prescription information and pill counts. 3. Blood, urine, and vitreous humor, when available, should be retained in all cases. Blood from the femoral vein is preferable to blood from other sites. 4. A toxicological panel should be comprehensive and include opioid and benzodiazepine analytes, as well as other potent depressant, stimulant, and anti-depressant medications. 5. Interpretation of postmortem opioid concentrations requires correlation with medical history, scene investigation, and autopsy findings. 6. If death is attributed to any drug or combination of drugs (whether as cause or contributing factor), the certifier should list all the responsible substances by generic name in the autopsy report and on the death certificate. 7. The best classification for manner of death in deaths due to the misuse or abuse of opioids without any apparent intent of self-harm is "accident." Reserve "undetermined" as the manner for the rare cases in which evidence exists to support more than one possible determination.